Examining the soil erosion responses to ecological restoration programs and landscape drivers: A spatial econometric perspective. (December 2020) - Jiang, Chong; Zhao, Lingling; Dai, Jialing; Liu, Haimeng; Li, Zhouyuan; Wang, Xinchi; Yang, Zhiyuan; Zhang, Haiyan; Wen, Meili; Wang, Jun
Abstract: Topsoil erosion is a widespread and major threat to terrestrial ecosystems that leads to environmental deterioration. Monitoring soil erosion dynamics and understanding the driving mechanisms are of great significance for optimizing ecological restoration programs and combating land degradation. We apply a widely used soil erosion assessment model to quantify the changes in soil erosion on the Loess Plateau (LP) in response to afforestation-induced vegetation cover and land use/cover changes. Furthermore, we examine the relationship between landscape metrics and soil erosion using spatial econometric approach. The results indicate that soil erosion in the LP substantially decreased through afforestation efforts, while the observed sediment load declined significantly as a result of soil and water conservation programs. A number of largescale ecological programs altered the spatial configuration and structural composition of the landscape from different aspects, which disturbed the formation and transportation of soil erosion, eventually resulting in a reduction in soil loss. The spatial association between landscape metrics and soil erosion indicated that properly fragmented landscapes can effectively decrease soil erosion. Due to the spatial spillover, soil erosion in one county can be affected by soil erosion in adjacent counties. Therefore, the spillover effect between counties should not be ignored, and the responsibility for formulating and implementing solutions to combat land degradation should not fall solely on individual local governments. Preferably, the cooperation between different regions should be strengthened as a critical way to improve the efficiency of programs combating land degradation. Highlights: The landscape pattern metric changes were quantified. The responses of soil loss to afforestation programs were revealed. The associations between soil erosion and landscape metrics were investigated via spatial econometric approach. The spatial spillover effects and their practical implications were discussed.